Organizational behavior and management - Ivancevich, John M. (McGraw-Hill / Irwin, 2005)
Organizational Behavior and Management’s new chapters examine perceptual biases and emotional dispositions along with management of workplace misbehavior, while interconnecting themes now integrate global practice, the balancing of work/life responsibilities, and benchmarking for competitive advantage.